Labor Migration as a Source of Institutional Change: Danish and Australian Construction Sectors Compared. (May 2023) - Arnholtz, Jens; Wright, Chris F.
In this article, the authors examine the role of labor immigration as a source of institutional change. They use a "most different systems" comparative case study analysis of the Danish and Australian construction sectors to examine the impact of increased labor migration on skill-sourcing practices in countries with distinct national skill formation and industrial relations institutions. Drawing on 73 interviews with industry stakeholders, the authors find that labor migration has produced liberalizing pressures in both Denmark and Australia, albeit in ways that differ from each other. The article contributes to comparative institutional scholarship by illustrating how labor migration can promote or support institutional change in a liberalizing direction by disincentivizing coordinated skill formation. Findings suggest that while national institutions mediate external pressures, such as labor migration, such pressures may affect the incentive structures that can either maintain or erode national institutions.